Durability and Mechanical Analysis of Basalt Fiber Reinforced Metakaolin–Red Mud-Based Geopolymer Composites - Ouiame Chakkor (Buildings)
Cement is widely used as the primary binder in concrete; however, growing environmental concerns and the rapid expansion of the construction industry have highlighted the need for more sustainable alternatives. Geopolymers have emerged as promising eco-friendly binders due to their lower carbon footprint and potential to utilize industrial byproducts. Geopolymer mortar, like other cementitious substances, exhibits brittleness and tensile weakness. Basalt fibers serve as fracture-bridging reinforcements, enhancing flexural and tensile strength by redistributing loads and postponing crack growth. Basalt fibers enhance the energy absorption capacity of the mortar, rendering it less susceptible to abrupt collapse. Basalt fibers have thermal stability up to about 800–1000 °C, rendering them appropriate for geopolymer mortars designed for fire-resistant or high-temperature applications. They assist in preserving structural integrity during heat exposure. Fibers mitigate early-age microcracks resulting from shrinkage, drying, or heat gradients. This results in a more compact and resilient microstructure. Using basalt fibers improves surface abrasion and impact resistance, which is advantageous for industrial flooring or infrastructure applications. Basalt fibers originate from natural volcanic rock, are non-toxic, and possess a minimal ecological imprint, consistent with the sustainability objectives of geopolymer applications. This study investigates the mechanical and thermal performance of a geopolymer mortar composed of metakaolin and red mud as binders, with basalt powder and limestone powder replacing traditional sand. The primary objective was to evaluate the effect of basalt fiber incorporation at varying contents (0.4%, 0.8%, and 1.2% by weight) on the durability and strength of the mortar. Eight different mortar mixes were activated using sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) solutions. Mechanical properties, including compressive strength, flexural strength, and ultrasonic pulse velocity (UPV), were tested 7 and 28 days before and after exposure to elevated temperatures (200, 400, 600, and 800 °C). The results indicated that basalt fiber significantly enhanced the performance of the geopolymer mortar, particularly at a content of 1.2%. Specimens with 1.2% fiber showed up to 20% improvement in compressive strength and 40% in flexural strength after thermal exposure, attributed to the fiber’s role in microcrack bridging and structural densification. Subsequent research should concentrate on refining fiber type, dose, and dispersion techniques to improve mechanical performance and durability. Examinations of microstructural behavior, long-term durability under environmental settings, and performance following high-temperature exposure are crucial. Furthermore, investigations into hybrid fiber systems, extensive structural applications, and life-cycle evaluations will inform the practical and sustainable implementation in the buildings.